Magnesium and Mental Health: A Review of Its Role in Anxiety, Sleep Disorders and Depression - Kowalczyk, Aleksandra; Pączek, Adrian Jan; Dyczek, Paweł; Staniszewska, Wiktoria; Hofman, Julia; Lach, Sylwia; Bednarek, Ilona (Journal of Education, Health and Sport, 2025)
Background. Magnesium is a key cation involved in neurotransmission, regulation of the hypothalamic–pituitary–adrenal axis and sleep–wake control. Observational studies and reviews suggest that low magnesium intake or status is linked with more depressive symptoms, anxiety and sleep disturbances, although results are not fully consistent. Objective. To summarise current evidence on the role of magnesium in depression, anxiety and sleep disorders in adults, with emphasis on human data and clinical practice. Methods. A narrative review of PubMed and other databases was performed. Priority was given to systematic reviews, meta-analyses, controlled trials and larger observational studies, including recent articles from the Journal of Education, Health and Sport. Results. Cohort and cross-sectional studies generally show an inverse association between dietary or serum magnesium and depressive symptoms. Some meta-analyses of trials report small-to-moderate reductions in depressive scores with oral magnesium, particularly in people with low baseline intake or somatic comorbidity, whereas others find limited benefit. For anxiety, trials suggest a possible anxiolytic effect, often with combination preparations, but evidence remains scarce and heterogeneous. In older adults with insomnia, small trials and reviews indicate modest improvements in sleep quality, and observational data link higher magnesium intake with fewer sleep complaints. Overall study quality is low to moderate. Conclusions. Suboptimal magnesium status appears to be associated with a higher burden of depressive, anxiety and sleep symptoms. Magnesium supplementation may provide modest, potentially clinically relevant benefit as an adjunct in selected adults, especially those with low intake or deficiency, but current data do not support its use as monotherapy. Further high-quality trials are needed to define optimal dosing, duration and target groups.